Approaching the Invisible - Angelika Thielsch (Forum Neue Medien in der Lehre Austria, 2017)
In situations of colliding discursive practices, their respective qualities can emerge. Based on this assumption, a research project has been conducted at the University of Göttingen that aimed at better understanding the hidden curriculum experienced by former exchange students. Using critical discourse analysis and an inductive approach as foundation, statements of this group have been collected and analysed. Implications regarding the experienced hidden curriculum were used to develop a reflective guideline for academic teaching staff. This paper introduces the theoretical and methodological foundation of my research and offers insight in the findings on how to approach challenges caused by the implicit nature of the hidden curriculum.